Crop Management Efficiency: Adaptation of promising crop management technologies to land and production environments in Babati, Tanzania - Maguta, Job Kihara; Kinyua, Michael Wanjohi; Sila, Andrew Musili (2023)
This study uses maize as the test crop. Maize is the key focus of most studies on crop response to micronutrients in SSA with a limited number of studies on wheat, rice, cowpea, sorghum, and soybean responses. Maize, constituting 45% of the cereal production in SSA in 2014, is the staple food crop (accounting for over 40% of the calories consumed in some countries such as Malawi and Zambia (http://www.fao.org/faostat/en/#data)) and the main component of food aid interventions in SSA (Leonardo et al. 2015). It is also grown under widely varying climatic, soil, and altitudinal conditions ranging from sea level (the coastal zones) to elevations above 2400 m (Sileshi et al. 2010). Methodology: Other technologies studied are: Mbilimbili and bio fortification